Employment arrangements and mental health in a cohort of working Australians: Are transitions from permanent to temporary employoment associated wtih changes in mental health? - Milner, A; Bentley, R; Krnjacki, L; LaMontagne, AD; Kavanagh, A (My University, 2014)
We investigated whether being in temporary employment, as compared with permanent employment, was associated with a difference in Short Form 36 mental health and whether transitions from permanent employment to temporary employment were associated with mental health changes. We used fixed-effects regression in a nationally representative Australian sample with 10 waves of data collection (2001–2010). Interactions by age and sex were tested. Two forms of temporary employment were studied: “casual” (no paid leave entitlements or fixed hours) and “fixed-term contract” (a defined employment period plus paid leave). There were no significant mental health differences between temporary employment and permanent employment in standard fixed-effects analyses and no significant interactions by sex or age. For all age groups combined, there were no significant changes in mental health following transitions from stable permanent employment to temporary employment, but there was a significant interaction with age (P = 0.03) for the stable-permanent-to-casual employment transition, because of a small transition-associated improvement in mental health for workers aged 55–64 years (β = 1.61, 95% confidence interval: 0.34, 2.87; 16% of the standard deviation of mental health scores). Our analyses suggest that temporary employment is not harmful to mental health in the Australian context and that it may be beneficial for 55- to 64-year-olds transitioning from stable permanent employment to casual employment.
Keywords: Gender -- Gender differences; Health -- Mental; Employment; Gender; Labour market; Health and wellbeing; Gender; Health; Employment; Mental; Gender differences; Health and wellbeing; Employment and unemployment; Gender